Effectiveness of lecture maker interactive media on students’ motivation and learning outcomes in respiratory system - Muhammad Syahrul; Husnaini Bahri; Syamsul Bahri HS; Monica Hetharia; Eva Moy Wonley; Riska Herlena S (University of Muhammadiyah Malang, 2026)
Background: Low student motivation and learning outcomes in biology remain a challenge in the learning process, particularly in complex topics such as the respiratory system. The use of interactive learning media is considered a potential strategy to enhance student engagement and understanding. Objectives: This study aimed to examine the effectiveness of Lecture Maker interactive media on students’ motivation and learning outcomes in the respiratory system topic. Methods: The research employed a quasi-experimental design with a pretest–posttest control group. The participants consisted of 50 eleventh-grade students divided into an experimental class and a control class. Data on learning motivation were collected using a questionnaire, while learning outcomes were measured through achievement tests. The data were analyzed using descriptive statistics and Analysis of Covariance (ANCOVA). Results: The results showed that students who learned using Lecture Maker interactive media had significantly higher motivation and learning outcomes compared to those who learned using conventional methods. These findings indicate that the use of Lecture Maker interactive media can effectively enhance students’ motivation and improve their learning outcomes in respiratory system learning. Therefore, interactive multimedia-based learning is recommended as an alternative approach to support biology learning in schools.